WIDESPREAD CUTANEOUS LESIONS DUE TO Sporothrix schenckii IN A PATIENT UNDER A LONG TERM STEROIDS THERAPY - SEVERO Luiz Carlos; FESTUGATO Moira; BERNARDI César; LONDERO Alberto Thomaz (Universidade de São Paulo (USP), 1999)
A case of sporotrichosis in a woman presenting 63 cutaneous lesions distributed all over the tegument is related. The patient had both humoral (Immunoglobulins) and cellular (Lymphocytes subpopulations) immunity within normal limits, but was under treatment with steroid during a long time (Prednisone 10 mg daily for 2 years), due to a sciatic pain. In addition a review of the Brazilian literature on this type of lesions was carried out and commented.